5PSQ-127 Assessing appropriate dosing of new oral anticoagulants: apixaban, dabigatran and rivaroxaban in a tertiary hospital. (14th March 2021) - Morla, G; Garcia Del Valle, I; Val, L; Marcos, P; Baronet, G; Garcia, M; Sanmartin, M; Prats, S; Santillo, D; Diaz, MA
Abstract : Background and importance: For a long time, vitamin K antagonists (VKAs), such as warfarin and acenocoumarol, have remained firstline anticoagulation therapy. Despite their effectiveness and low cost, the need for frequent monitoring and dose adjustments has highlighted the importance of introducing into clinical practice new oral anticoagulants (NOACs) to increase safety and obtain more predictable results. Aim and objectives: The aim of the study was to determine dose adequacy of three new oral anticoagulants (apixaban, dabigatran and rivaroxaban) prescribed in clinical practice. Material and methods: An observational prospective study was conducted in a tertiary hospital over a 6 month period. All patients with a prescription for apixaban, dabigatran or rivaroxaban were eligible for the study. Demographic (age, gender, medical history) and clinical (weight, NOAC type and dose, diagnosis and renal function calculated with the MKP-EPI form) data were recorded in a chart, and dose adequacy was assessed and reviewed by two different investigators. The results were analysed using a multivariable logistic regression technique with a 95% significance level. Results: After excluding 3 patients due to incomplete data, 138 patients, 56% men, were recruited. From these, 40% of the patients were prescribed apixaban, 25% dabigatran and 34% rivaroxaban. The statistical analysis adjusted by sex and age showed that the risk of inadequacy was significant when using apixaban (p<0.001, OR 8.4) and dabigatran (p<0.006, OR 7.0). This could be explained by the fact that the most prevalent diagnosis was auricular fibrillation. In this indication, rivaroxaban is adjusted by creatinine clearance while apixaban is adjusted by weight, age and clearance, and dabigatran by age, concomitant treatment with verapamil and clearance. Lower doses were significantly inadequate compared with higher doses (apixaban 2.5 mg/12 hours (p<0.000), dabigatran 110 mg/12 hours (p<0.002) and rivaroxaban 15 mg/12 hours (p<0.036)). Rivaroxaban was the nearest to an adequate prescription. Conclusion and relevance: In conclusion, it seems that at least for auricular fibrillation, rivaroxaban constitutes the agent with the best adequacy, probably due to its simpler adjustment. Furthermore, with the three drugs, lower doses tended to be less adequate than higher doses, which raises the question of whether patients are under dosed. More training is needed to correctly prescribe this group of drugs. References and/or acknowledgements: Conflict of interest: No conflict of interest